Analisis Postur Kerja Operator dengan Metode Rula di Area Gas Cutting - irwan Pegiardi; Firdanis Setyaning Handika; Supriyadi Supriyadi (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2017)
The gas cutting area has several jobs that are risky to the operator, such as activities with squatting, bending positions. This study aims to determine the risk of work in the gas cutting area as a basis for improving work posture. The method used is RULA (Rapid Upper Limb Assessment) is a research method for investigating disorders of the upper limbs. By measuring the group A score and group B score. Based on the results of the RULA value in the process of operating the machine with a sitting position with a score 3. clearing the cutting plate with a bent position with a score of 5, and the highest score 6 in the grinding plate cutting. To reduce pain in the neck, torso, and arms, operators should not do work postures that cause pain in the body for a long time.